Self, no self? : perspectives from analytical, phenomenological, and Indian traditions - Siderits, Mark, 1946-; Thompson, Evan; Zahavi, Dan (Oxford University Press, 2010)
'Self, No Self?' is the first book of its kind. It brings together leading philosophical scholars of the Indian and Tibetan traditions with leading Western philosophers of mind and phenomenologists to explore issues about consciousness and selfhood from these multiple perspectives.